Automatic Clinic Measures and Comparison of Heads using Point Clouds - Oliveira, Pedro (2020)
Nowadays the necessity to automate processes is increasing. One of the areas where automation can help is medicine. This document shows a process of how to analyze a point cloud of a head to define reference points and extract important measures. It also describes a head comparison process to compare a base head with a set of heads and find out the most similar one. The extracted measures will be applied for the diagnose and treatment of positional plagiocephaly disease that affects babies. A solution, integrating different technologies, has a graphical interface to present the measures retrieved from the point clouds of the heads and the results of heads comparison. The interface allows the visualization of the point clouds of the heads and helps to see the difference between heads. With the auxiliary of this solution it is possible to create a more adequate orthosis to treat each patient with positional plagiocephaly.